Model Pembelajaran Role Playing dalam Meningkatkan Fokus Peserta Didik - Afri Naldi; Reval Oktaviandry; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2024)
This writing aims to enhance the focus of learners in the learning process by employing the role playing learning model. The role playing learning model involves activities where learners take on specific character roles. Through this simulation, the goal is to develop problem-solving skills and behaviors, as well as to delve into the subject matter with a unique approach. Data compilation in this writing is conducted through literature review, utilizing sources from journals, books, and other scholarly works. By employing this learning model, it will enhance the engagement and focus of learners in the learning process.